PENGARUH PENDIDIKAN, KEBIASAAN MEROKOK, DAN KEPATUHAN AKTIVITAS FISIK TERHADAP RISIKO HIPERTENSI DI WILAYAH KERJA PUSKESMAS RASAU JAYA - Marsha Julita Dwi Pratiwi; Dedi Alamsyah; Selviana; Helfi Nolia (Poltekkes Kemenkes Medan, 2025)
Hypertension is a chronic health problem that often goes undetected and can lead to serious complications such as stroke, heart failure, and kidney disorders. This study aims to analyze the relationship between educational level, physical activity, and smoking habits with the incidence of hypertension in the working area of Rasau Jaya Public Health Center. A quantitative design with a cross-sectional approach was used, involving 252 respondents who were all included as the study sample. Data were collected through questionnaires and interviews, then analyzed using the Chi-Square test with a significance level of 0.05. The results showed that the majority of respondents were female (82.1%), adults, and had a low educational level (93.7%). A total of 59.5% of respondents had uncontrolled hypertension. Bivariate analysis revealed a significant relationship between educational level and hypertension control status (p = 0.034), with respondents who had lower education being more likely to experience uncontrolled hypertension. In contrast, no significant relationship was found between physical activity and hypertension (p = 0.294), nor between smoking habits and hypertension (p = 1.000). In conclusion, educational level influences the ability of individuals to manage their hypertension, while physical activity and smoking habits do not show significant associations in this study population.